THE EFFECTIVENESS OF TIMELINE STORY POSTER FOR ISLAMIC HISTORY SUBJECT - Nurahmah, Riska Hanan (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2023)
Islamic History courses are often considered boring and uninteresting, which has an impact on student learning outcomes. Especially if the learning media used is considered monotonous and not creative. This research aims to test the effectiveness of the Timeline Story Poster learning media on student learning outcomes in Islamic history courses. The population is 235 students and the sample is 70 students. The results of the Mann-Whitney test using SPSS 16 show that there are differences in learning outcomes between the control class and the experimental class. In other words, the Timeline Story Poster media can be considered effective for use in Islamic history courses. Keywords: Islamic history, media, timeline story poster, learning outcomes